Trends in macroevolution - Harmon, Luke (Henry Stewart Talks, 2023)
The pace of macroevolution, Galapagos finches, Adaptive radiation, High speciation rates are not extended over deep time, Living fossils, The paradox of stasis, Rate-scaling pattern